A method for the confirmation and identification of drugs of misuse in urine using solid phase extraction and gas-liquid chromatography with mass spectrometry. Issue 4 (April 1998) - Galloway, J H; Ashford, M; Marsh, I D; Holden, M; Forrest, A R
Abstract : A method is described for the confirmation/identification of a range of commonly misused drugs in urine samples. The method has been used for two years without problems for a range of purposes including hospital/clinic drugs of misuse screening and for toxicology in coroner's cases. Urine samples which have given a positive result on immunochemical screening for a particular drug group or groups (for example, opiates) can be processed with identification of the drugs present using a single procedure. Bond ElutCertify columns are used for the extraction of drugs from the samples followed by propionylation and gas chromatography with mass selective detection.